Review of the Oriental planthopper genus Flata Fabricius (Hemiptera: Fulgoroidea: Flatidae) with the description of five new species - Peng, Ling-Fei; Fletcher, Murray J.; Zhang, Ya-Lin (Zootaxa, 2012)
In this paper the oriental planthopper genus Flata Fabricius, 1798 is reviewed. The genus is redescribed and all orientalspecies described and illustrated, including five new species: F. orientala sp. nov., F. pinga sp. nov., F. sinuata sp. nov.,F. taiwana sp. nov. and F. truncata sp. nov. from tropical or subtropical regions of China. A key to the oriental species ofthe genus and a checklist of species are provided. Three non-oriental species currently included in Flata are treated as being of uncertain generic affinity.